2009
DOI: 10.1002/hep.23203
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions of occludin and claudin‐5 in brain endothelial cells in vitro and in brains of mice with acute liver failure†

Abstract: Brain edema in acute liver failure (ALF) remains lethal. The role of vasogenic mechanisms of brain edema has not been explored. We previously demonstrated that matrix metalloproteinase-9 (MMP-9) contributes to the pathogenesis of brain edema. Here, we show that MMP-9 mediates disruptions in tight junction (TJ) proteins in vitro and in brains of mice with ALF. We transfected murine brain endothelial cells (ECs) with MMP-9 complementary DNA (cDNA) using pc DNA3.1 (؉)/Myc-His A expression vector. Tissue inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 47 publications
13
108
1
1
Order By: Relevance
“…As earlier results of our group suggest that the effect of fructose on occludin protein levels in the duodenum is not dependent upon an alteration of occludin mRNA expression 20 and as results of recent studies suggest that occludin protein levels are also regulated through MMPs, 21,22 we determined mRNA expression of MMP-9 and MMP-13 as well as protein levels of TIMP-1 in the duodenum. Expressions of MMP-9 ( Figure 7a) and MMP-13 ( Figure 7b) were considerably induced in the duodenum of fructose-fed groups; however, a similar effect of the fructose feeding was not detected in metformin-treated mice.…”
Section: Effect Of Metformin Treatment On Timp-1 Protein and On Mmp-9mentioning
confidence: 74%
See 1 more Smart Citation
“…As earlier results of our group suggest that the effect of fructose on occludin protein levels in the duodenum is not dependent upon an alteration of occludin mRNA expression 20 and as results of recent studies suggest that occludin protein levels are also regulated through MMPs, 21,22 we determined mRNA expression of MMP-9 and MMP-13 as well as protein levels of TIMP-1 in the duodenum. Expressions of MMP-9 ( Figure 7a) and MMP-13 ( Figure 7b) were considerably induced in the duodenum of fructose-fed groups; however, a similar effect of the fructose feeding was not detected in metformin-treated mice.…”
Section: Effect Of Metformin Treatment On Timp-1 Protein and On Mmp-9mentioning
confidence: 74%
“…Indeed, it has been suggested before by the results of in-vitro and in-vivo studies of others that MMPs are involved in the degradation of occludin. 21,22 Furthermore, it has been shown that MMPs and TIMPs levels are altered in situations of insulin resistance. 34,35 However, mechanisms involved in these alterations and the protective effects of metformin herein remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the same models, alterations in the expression of the major BBB tight junction proteins (occludin, claudin-5, zonula occludens 1 and 2) have been observed (Chen et al, 2009, Lv et al, 2010, Sawara et al, 2009and Shimojima et al, 2008. However, in galactosamine-induced ALF in the rabbit, it was reported that capillary endothelial cells appeared normal, and no evidence of brain extravasation to horseradish peroxidase was observed (Traber et al, 1987), contradicting the anterior data.…”
Section: Vasogenic Versus Cytotoxic Brain Edema In Alf and Cldmentioning
confidence: 82%
“…This treatment concept is based upon the presumption of an intact BBB, which may not be the case in severe ALF with high HE score [7,21]. The present results should therefore lead to a discussion about the Kristiansen, R.G.…”
Section: Discussionmentioning
confidence: 84%